Analysis of Indonesian Public Perception on the Influence of American Food Brands with the Indonesia-America Cooperation Relationship Using SEM-PLS - Aqil Azmi, Reswara; Nadhira Safa, Kamiilah; Marshanda, Aprilia; Shalwa Oktavrilia, Kusuma; M. Fariz Fadillah, Mardianto; Ardi, Kurniawan (INTI International University, 2024)
Globalization has removed barriers between countries, particularly in the field of food. One of the main impacts of this phenomenon is the entry of foreign food and beverage brands into domestic markets, including brands from the United States. The United States (US) supports Israel in its conflict with Palestine, which is contrary to Indonesia's stance. Therefore, an analysis was conducted on the perception of Indonesian society towards American brands and how this affects the bilateral cooperation between the two countries. The method used was descriptive quantitative, and data analysis was performed using Structural Equation Modeling Partial Least Square (SEM-PLS) with a sample of 200 respondents. The results of this study showed an R-square value of 10.22% without a mediating variable and 49.87% when including a mediating variable. This value indicates that incorporating the mediating variable into the model increases the explained variability of the model to 49.87%, while the remainder can be explained by other variables.